A systematic review of research on nontraditional students reveals inconsistent definitions and a need for clarity: focus on U.S. based studies - Brozina, Cory; Johri, Aditya; Chew, Alanis (Frontiers in Education, 2024)
BackgroundThe term “nontraditional students” (NTS) is widely used in higher education research, but its definition varies across studies.ObjectivesThis systematic literature review aims to examine how researchers define NTS in U.S.-based studies and identify potential definitional issues.MethodsWe conducted a systematic review following PRISMA guidelines, searching EBSCO databases (Education Research Complete, Education Full Text, and ERIC) for peer-reviewed articles published between 2018 and 2022. We analyzed 65 papers that met our inclusion criteria to assess the definitions used for NTS. In this systematic literature review we focus on the definitional issues related to how researchers use the term nontraditional students in US-based studies. We review 65 papers from search results containing 432 papers to understand how researchers define nontraditional students. Of the 65 papers reviewed fully, 33 papers included a specific definition of nontraditional students, 15 included an unspecified definition of nontraditional students, and 17 papers did not include a clear definition at all. Our work suggests that researchers use a clearer definition, such as from the NCES, to define nontraditional students and focus their attention on the seven categories given by NCES.